THERE IS A HUMAN! A MANIFEST FOR PUNISHMENT BIOPOLITICS, BIOETHICS AND BIOPOWER - Silva, Luciano Braz [UNESP] (Univ Estado Rio Janeiro, 2018)
The contemporary impels us to resolve those issues still widespread in the fields of theoretical and applied ethics, not only from the philosophical disciplines, but the domains of knowledge made by science and the technical knowledge. Today bioethics takes a genuinely philosophical status, critical and emancipatory, with a transdisciplinary scope by nature, where philosophers, lawyers, doctors and social scientists are called to intervene and maintain a permanent dialogue. If one of the oldest meanings of Ethics is to be synonymous with dwelling, housing and living way, this article intends to revisit this tradition to devote to the tasks and challenges of a new and still later confrontation. Here, the player will be faced with reflections on philosophical ethics and acute questions of political philosophy and law, always tied to genuinely arising nature prospects of biopolitics and bioethics order to rethink the identity of the human.
Keywords: Ethics; biopolitics; bioethics; Human life